PENGARUH MEDIA MESIN HITUNG PEMBAGIAN (MHP) TERHADAP KEAKTIFAN DAN HASIL BELAJAR SISWA PADA MATERI PEMBAGIAN KELAS III DI SDN BURNEH 1 BANGKALAN - Idah, Nurul Af; Pratiwi, Siska (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to see the influence of division calculating machine media on the activeness and learning outcomes of class III students at SDN Burneh 1 Bangkalan, because when teachers teach they only use the lecture method, which makes learning monotonous and boring. Apart from that, the average score for daily mathematics tests is still below the minimum completeness criteria (70), namely 65, 32. This research method uses a quantitative research method using a one group pretest posttest design. This research was conducted at SDN Burneh 1 Bangkalan. The population in this study were all students in class III-C of SDN Burneh 1 Bangkalan, and the sample used was 30 students using a saturated sample. This research uses instruments in the form of question sheets and observation sheets. The data analysis techniques used in this research are validity test, reliability test, normality test, hypothesis test paired sample t-test and MANOVA test. Based on the results of the Manova test or Multivariate Tests, it can be seen that the sig value obtained is 0.000 < 0.05, HO is rejected and Ha is accepted, so it can be concluded that there is an influence of the use of division calculating machine media on the activeness and learning outcomes of class III students at SDN Burneh 1 Bangkalan.